2016
DOI: 10.1007/s00181-016-1152-y
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric approach to identifying a subset of forecasters that outperforms the simple average

Abstract: Empirical studies in the forecast combination literature have shown that it is notoriously di cult to improve upon the simple average despite the availability of optimal combination weights. In particular, historical performance-based combination approaches do not select forecasters that improve upon the simple average going forward. This paper shows that this is due to the high correlation among forecasters, which only by chance causes some individuals to have lower root mean squared errors (RMSE) than the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Additionally, we follow the approach suggested by Bürgi and Sinclair (2017). They calculate for each institution a dummy variable "that takes value 1 in a given period if that forecaster has a lower squared error in that period than the simple average and 0 otherwise."…”
Section: Testing For Long-run Superioritymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we follow the approach suggested by Bürgi and Sinclair (2017). They calculate for each institution a dummy variable "that takes value 1 in a given period if that forecaster has a lower squared error in that period than the simple average and 0 otherwise."…”
Section: Testing For Long-run Superioritymentioning
confidence: 99%
“…Finally, we adopt the Bürgi and Sinclair (2017) approach outlined above to select successful forecasters for a given year. To this end, we refer to the last five years and demand that an institution should have been better than the average at least half of the time, i.e., the percentage threshold in our case is 50 %.…”
Section: Selecting Successful Forecastersmentioning
confidence: 99%
“…Disagreement however will become substantially larger when recessions are anticipated by at least some forecasters than in normal periods when forecasters tend to bunch together (e.g. see Bürgi and Sinclair (2017)).…”
Section: Modelmentioning
confidence: 99%
“…We find that different combination algorithms excel in different kinds of unstable environments: Compared with the rest of the methods we examined in the paper, the one proposed in Sancetta (2010) is more robust to breaks in performances due to idiosyncratic errors; the AFTER algorithms are more robust to unpredictable and sudden aggregate shocks; and the approach in Bürgi & Sinclair (2017) is quicker in adapting to changes in individuals'…”
Section: Introductionmentioning
confidence: 99%
“…The results, therefore, are closer to those based on equal weights. In addition, we examine the performance of the nonparametric approach proposed in Bürgi & Sinclair (2017), where the authors suggested that only the forecasts with a proven track record of outperforming simple averaging should be combined.…”
Section: Introductionmentioning
confidence: 99%